Corticosteroids and rising tide in femoral head avascular necrosis following COVID-19: A critical analysis - Demir, Levent; Avcı, Mustafa; Yücel Uçarkuş, Tuba; Kahraman, Murat; Öztürk, Mustafa; Şahingöz Tahta, Mehtap; Kılıç, Selahattin (The European Research Journal, 2025)
Objectives: During the COVID-19 pandemic, increased corticosteroid use to treat severe cases has been linked to a rise in femoral head avascular necrosis (FHAVN) cases post-recovery. This study evaluated FHAVN patients referred to an outpatient clinic after COVID-19, focusing on the severity of FHAVN related to corticosteroid use, and aimed to connect the drug dosage, and disease grade. Methods: The study was prospectively designed. Patients diagnosed with FHAVN who received corticosteroids for COVID-19 were included. Data collected included demographic information, medical history, corticosteroid dosage, and magnetic resonance imaging results for radiological grading. Results: A total of 48 patients were evaluated, with a mean age of 46.13 years. A significant majority (81.3%) of the respondents had bilateral FHAVN. The patients received a mean prednisolone equivalent dose of 1295.16±857.98 mg over approximately 18 days. This study found a significant positive correlation between the severity of FHAVN and the dosage and total corticosteroid treatment time. Conclusions: The findings indicate that the severity of FHAVN is correlated with corticosteroid use. Although corticosteroids have shown benefits in severe COVID-19 cases, their prolonged and high-dose administration poses risks, including the development of FHAVN.